2017
DOI: 10.15740/has/au/12.techsear(3)2017/718-724
|View full text |Cite
|
Sign up to set email alerts
|

Per se performance in tomato (Solanum lycopersicum L.) for yield attributes, yield and quality

Abstract: to study the genetic parameters, heterosis, combining ability, gene action governing the inheritance of the traits, correlation co-efficient analysis, path co-efficient analysis and inbreeding depression. Ten parents (EC-165749, EC-157568, EC-164838, LE-56, LE-62, LE-64, LE-65, LE-66, LE-67 and LE-68) were crosssed in diallele mating design (without reciprocals). The resultant 45 F 1 's were evaluated along with their parents and two standard checks (Siri and US-618) for plant height (cm), number of primary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…Number of fruits directly affects the total fruit yield per plant, so this character is very important for fruit yield. These findings are in close agreement with (Dundi and Madalagaeri,1991;Kumar et al,2006;Asati et al,2007;Saleemet al,2009;Kumari and Sharma ,2011;Shankar et al,2013;Solieman et al,2013;Madhaviet al,2013;Syarifah et al,2016;Savita and singh,2017;VRamana et al, 2018;and Pramod et al,2019). Midparent heterosis of total fruit yield ranged from -4.65 percent (P4xP5) to 11.55 percent (P1xP5) and better parent heterosis from -3.55 percent (P1xP4) to 7.08 percent (P1xP5).Total fruit yield per plant is the most important trait which deserve highest consideration in any breeding program.…”
Section: Heterosissupporting
confidence: 82%
See 2 more Smart Citations
“…Number of fruits directly affects the total fruit yield per plant, so this character is very important for fruit yield. These findings are in close agreement with (Dundi and Madalagaeri,1991;Kumar et al,2006;Asati et al,2007;Saleemet al,2009;Kumari and Sharma ,2011;Shankar et al,2013;Solieman et al,2013;Madhaviet al,2013;Syarifah et al,2016;Savita and singh,2017;VRamana et al, 2018;and Pramod et al,2019). Midparent heterosis of total fruit yield ranged from -4.65 percent (P4xP5) to 11.55 percent (P1xP5) and better parent heterosis from -3.55 percent (P1xP4) to 7.08 percent (P1xP5).Total fruit yield per plant is the most important trait which deserve highest consideration in any breeding program.…”
Section: Heterosissupporting
confidence: 82%
“…(Singh et al, 2005;Asati et al, 2007;and Singh and Asati, 2011) also reported positive heterosis for average fruit weight in tomato. Similar results were also obtained by (Dod et al,1995;Kumar et al, 2009;Kumari and Sharma, 2011;Shankar et al, 2013;Solieman et al,2013;Madhavi et al, 2013;Syarifah et al,2016;Vramana et al,2018;and Pramod et al,2019). Heterosis for number of Fruits / plant was found in a range of -25.63 % (P 4 x P 5 ) to 13.97 % ( P 1 x P5) for mid parent and -13.76 % ( P2 x P5) to -40.21 % ( P4 x P5 ) over better parent .…”
Section: Heterosissupporting
confidence: 78%
See 1 more Smart Citation
“…The cross VRT-18×H-86 exhibited the highest significant negative standard heterosis at -21.50% followed by VRT-50×SEL-7 at -16.53% and VRT-50×H-86 at -13.90%. Negative heterosis for the trait days to 50% flowering is observed by Hannan et al (2007) [4] , Islam et al (2010) [5] , Ahmad and Quamruzzaman (2011) [6] , Kumar et al (2012) [7] Khan and Jindal (2016) [8] , Ramana et al (2018) [9] and Sah et al (2020) [10] in tomato. With regards to plant height, VRT-51×SEL-7 (44.5%) displayed the highest level of significant positive relative heterosis followed by H-24×H-86 (41.63%) and VRT-74×SEL-7 (34.47%) as indicated in Table 1.…”
Section: Resultsmentioning
confidence: 98%
“…Similar trends of earliness were reported by Padma e al. (2002), Shanker et al (2013), Madhavi et al (2013) and Ramana et al (2018).…”
Section: Resultsmentioning
confidence: 99%